Development Status and Future Prospects of Reference Materials for the Leather and Footwear Industry in China - Jiyu LIANG; Keshuai REN; Wei ZHOU; Chunhua WANG; Jun SANG; Wei LIN (Pige Kexue Yu Gongcheng)
As the leather and footwear industry enters a new phase of high-quality development, the demand for standardization within the industry is steadily increasing. With the support of national policies promoting the development of reference materials, leather and footwear reference materials, as physical standards, have gradually become an essential component of standardization efforts in the leather and footwear industry. They also serve as vital tools for enhancing the inspection and testing technologies across the entire industry. This paper provided an overview of the development history of reference materials both domestically and internationally and offered a detailed analysis of the current state of reference materials in the leather and footwear industry. It examined aspects such as the construction of reference material systems, the characteristics of reference materials, and existing challenges, and finally provided suggestions for the future development trends of reference materials in the leather and footwear sector.